2022
DOI: 10.1111/ans.17655
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Victorian COVID‐19 lockdowns on the presentation and management of acute appendicitis

Abstract: Backgrounds The COVID‐19 pandemic presents ongoing challenges for healthcare. Stay at Home orders (‘lockdowns’) and community fears have been suggested to create reluctance to seek healthcare. We aimed to determine whether the rates of perforated appendicitis and negative appendicectomy have been affected by the pandemic, and to analyse the effect of lockdowns on the management of acute appendicitis in Victoria. Methods We conducted a retrospective audit of emergency appendicectomies performed under adult Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In our cohort, the negative appendicectomy rate nearly halved during the pandemic to 5.7%, whilst the rate of CT prior to operation increased by approximately 10%. Studies during the pandemic also noted the same significant reduction in negative appendicectomy, and have reported a rate as low as 0% [ 23 , 25 , 26 , 29 ]. Their studies also identified higher rates of CT use.…”
Section: Discussionmentioning
confidence: 82%
“…In our cohort, the negative appendicectomy rate nearly halved during the pandemic to 5.7%, whilst the rate of CT prior to operation increased by approximately 10%. Studies during the pandemic also noted the same significant reduction in negative appendicectomy, and have reported a rate as low as 0% [ 23 , 25 , 26 , 29 ]. Their studies also identified higher rates of CT use.…”
Section: Discussionmentioning
confidence: 82%
“…Large-scale lockdowns were used to prevent extensive community transmission of COVID-19 in Australia. In the state of Victoria, there were six lockdowns totaling 242 days between 2020 and 21 (Rajagopalan et al, 2022 ). Except for a 2-week period during the 6th lockdown, construction industries were permitted to work with restrictions on workforce size (Victorian Building Authority, 2021 ).…”
Section: Methodsmentioning
confidence: 99%